2017
DOI: 10.4097/kjae.2017.70.2.203
|View full text |Cite
|
Sign up to set email alerts
|

Reversal with sugammadex for rocuronium-induced deep neuromuscular block after pretreatment of magnesium sulfate in rabbits

Abstract: BackgroundMagnesium sulfate (MgSO4) has been used in the treatment of pre-eclampsia, hypertension and arrhythmia. Magnesium enhances the neuromuscular block of rocuronium. This study has been conducted to evaluate the reversal efficacy of sugammadex from deep rocuronium-induced neuromuscular block (NMB) during consistent pretreatment of MgSO4 in rabbits.MethodsTwenty-eight rabbits were randomly assigned to four groups, a control group or study groups (50% MgSO4 150–200 mg/kg and 25 mg/kg/h IV), and received ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Thus, changes in magnesium concentration (from 1 to 4 mM) did not seem to affect recovery mediated by sugammadex. This result is consistent with that of a rabbit study in which sugammadex at doses of more than 4 mg/kg was associated with similar recoveries among magnesium-infused and non-infused groups of rabbits [ 21 ]. It is likely that the dose of sugammadex is more important than the magnesium concentration in terms of clinically acceptable limits; neuromuscular transmission monitoring is essential to ensure that sufficient sugammadex is administered.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, changes in magnesium concentration (from 1 to 4 mM) did not seem to affect recovery mediated by sugammadex. This result is consistent with that of a rabbit study in which sugammadex at doses of more than 4 mg/kg was associated with similar recoveries among magnesium-infused and non-infused groups of rabbits [ 21 ]. It is likely that the dose of sugammadex is more important than the magnesium concentration in terms of clinically acceptable limits; neuromuscular transmission monitoring is essential to ensure that sufficient sugammadex is administered.…”
Section: Discussionsupporting
confidence: 91%
“…With the significant impact of magnesium on neuromuscular blockade and subsequent reversal with acetylcholinesterase inhibition, its effect on reversal with sugammadex has been questioned. Animal models demonstrate mixed results when investigating whether raising plasma magnesium levels impacts the dose of sugammadex needed to reverse neuromuscular blockade [ 80 , 81 ]. Aside from one observational study that suggested patients may need sugammadex doses exceeding 14 mg/kg in the presence of a magnesium infusion for the treatment of HELLP syndrome [ 82 ], the remaining literature suggests that reversal with standard doses of sugammadex is not prolonged in patients receiving clinically-relevant doses of intravenous magnesium.…”
Section: Reviewmentioning
confidence: 99%
“…Further, it was reported that pretreatment with magnesium did not significantly affect sugammadex reversal time for moderate NMB [ 32 ]. In addition, magnesium did not affect the reversal effects of sugammadex in animal studies [ 33 , 34 ]. However, administration of magnesium after rocuronium‐induced NMB reversal with sugammadex may lead to recurarization, requiring continuous neuromuscular monitoring [ 35 ].…”
Section: Use Of Sugammadex In a Special Clinical Situationmentioning
confidence: 99%